Comparative Study of Alveolar Bone Density in Various Segments of the Jaw Using Micro-CT Scanning. - Rashid, Mohammed Enamur (Bangladesh Journal of Medical Science, 2025)
Alveolar bone density plays a critical role in the success of dental implants and other prosthetic treatments. Precise evaluation of bone density in various segments of the jaw is essential for planning such procedures. Micro-computed tomography (Micro-CT) offers a highly accurate method to assess bone density, providing detailed insights into structural variations across different regions of the jaw. Materials and Methods: A total of 40 human mandibles and maxillae from cadaveric specimens were analyzed. The study included 20 male and 20 female specimens aged between 35 and 60 years. Using a high-resolution Micro-CT scanner, bone density was measured in three segments of the jaw: anterior, middle, and posterior. The data were assessed using Hounsfield Units (HU), and statistical analysis was performed using ANOVA to identify significant differences between the segments. Results: The mean bone density values (in HU) were as follows: Anterior region: 1300 ± 50 HU, Middle region: 1100 ± 40 HU, Posterior region: 900 ± 30 HU. Significant differences were observed between the anterior and posterior segments (p < 0.001) as well as between the anterior and middle segments (p < 0.05). The anterior segment exhibited the highest bone density, making it the most suitable site for implant placement in terms of primary stability. Conclusion: Micro- CT scanning demonstrated that alveolar bone density varies significantly across different segments of the jaw. The anterior region showed the highest density, suggesting its preference for implant placement. BJMS, Volume: 24. Supplementary Issue 2025, Page : 66-68